The Illinois Detective Agency: the case of Duffy's revenge [large type] - Wolfe, Ethan J. (Wheeler large print western series., 2023)
"Book three picks up where book two leaves off, with the murder of James Duffy's future wife in the town of Miles City, Montana. The Agency is naturally outraged and Agency Director Charles Porter sends James Duffy, Jack Cavill, and Joseph Goodluck to Miles City to investigate. Porter and his personal assistant, Miss Potts, also make the trip. In Miles City they meet with Sheriff Bates, who provides details of what happened. During the Miles City founding day celebration, Duffy's future wife, Sylvia Trent, attended the dance with a family friend. Sometime during the festivities, Sylvia went missing and wasnt found until the next day by a stable hand in the loft. Sylvia was raped and murdered by strangulation. An investigation leads to one suspect, a man named Robert Peru. A cowboy at the Trent Ranch, Peru disappeared after the dance, along with four of his friends. Peru rides a very distinctive, Appaloosa horse. Peru, a Mormon, had family in Salt Lake City, Utah, and having no other leads, that is where Duffy, Cavill, and Goodluck go""--